Making Merchants The Cultural Construction of a Merchant Class in Early Modern Germany - Howell, Martha C. (Cambridge Cambridge University Press, 2025)
List of Figures; Acknowledgements; Note on Currencies and Monetary Values; Introduction; Part I. The Selbstzeugnisse in Context: 1. The Historiographical Context; 2. The Sociocultural Context; 3. The Problem of Merchants' Self-perception; Part II. The Merchants' Selbstzeugnisse: 4. The Selbstzeugnisse at the Center of this Study; 5. Mercantile Honor/Dishonor; 6. Merchants and the Urban Political Elite; 7. Living 'Noblement'; 8. Family; 9. Faith; Part III. Merchants in the Round: 10. Renaissance Men; 11. The Performance of Manhood; 12. Capitalism and Class; Bibliography; Index.
E-Book / Zugriff nur im Lesesaal
Keywords: 1500-1600; Kultur; Kaufmann; Deutschland